Evaluation of the quadriceps muscle length to femoral length ratio in small breed dogs with medial patellar luxation. Issue 4 (7th March 2023) - Nagahiro, Yukari; Murakami, Sawako; Shimada, Masakazu; Kanno, Nobuo; Harada, Yasuji; Hara, Yasushi
Abstract: Objective: To determine the quadriceps muscle length (QML) to femoral length (FL) ratio (QML/FL) and its associated factors in small breed dogs with medial patellar luxation (MPL) and to compare the differences in the QML/FL between MPL grades. Study design: Retrospective study. Sample population: Small breed dogs (<10 kg) with MPL: 78 dogs (134 limbs). Methods: Medical records and computed tomography (CT) images from 2008–2020 were reviewed. Furthermore, age, bodyweight, sex, laterality, MPL grade, femoral inclination angle (FIA), femoral torsion angle (FTA), anatomical lateral distal femoral angle (aLDFA), and patellar ligament length to patellar length ratio were included in the regression analysis to determine the factors associated with QML/FL. Each measurement parameter was compared among the four MPL grade groups. Results: The final model demonstrated that the QML/FL increased with increasing age ( p  = .004) and decreased with increasing FTA and aLDFA ( p  = .015 and p  < .001, respectively). The MPL grade IV group had a lower QML/FL than the grade I, II, and III groups ( p  = .002, p  < .001, and p  < .001, respectively). Conclusion: Among small breed dogs, those with MPL grade IV had a shortened QML associated with femoral deformities. Clinical significance: Noninvasive evaluation of the QML/FL improves our understanding of the length mismatch between the quadriceps muscle and the femur.